2013
DOI: 10.1088/0963-0252/22/2/025006
|View full text |Cite
|
Sign up to set email alerts
|

Negative-ion surface production in hydrogen plasmas: modeling of negative-ion energy distribution functions and comparison with experiments

Abstract: Negative ions in low-pressure plasma sources are created either in the plasma volume by dissociative attachment or, at the plasma surface interaction due to surface ionization of backscattered or sputtered particles. Negative-ions formed on surfaces are accelerated towards the plasma by the sheath. They can influence the plasma kinetics through collisions with plasma species, or are self-extracted from the plasma thanks to the energy acquired in the sheath. Self-extraction of negative-ions can affect processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(92 citation statements)
references
References 38 publications
1
91
0
Order By: Relevance
“…Surface negative ion production measurements are performed in the diffusion chamber of a plasma reactor. We only briefly describe the experiment here, as details can be found elsewhere [83,84]. The plasma is generated at 1 or 2 Pa, either by capacitive coupling from an external antenna using a 20 W 13.56 MHz generator, or at 1 Pa by an Electron Cyclotron Resonance antenna driven by a 60 W, 2.45 GHz generator.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface negative ion production measurements are performed in the diffusion chamber of a plasma reactor. We only briefly describe the experiment here, as details can be found elsewhere [83,84]. The plasma is generated at 1 or 2 Pa, either by capacitive coupling from an external antenna using a 20 W 13.56 MHz generator, or at 1 Pa by an Electron Cyclotron Resonance antenna driven by a 60 W, 2.45 GHz generator.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Both modelling methods that will be presented later require knowledge of ion trajectories inside the sheaths in front of the mass spectrometer and in front of the sample as a function of ion emission angle and energy. The experimental arrangement has been designed in order to ensure planar sheaths in front of mass spectrometer and sample (the biased surface is much larger than the sample surface to prevent edge effects) [83]. In this situation, the local electric field in the sheaths can be calculated using Child Langmuir law knowing the electron density and temperature (from Langmuir probe measurements) and the surface bias.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, absolute ion flux measurements are very complicated due to a nontrivial dependence of the total system transparency for ions having different mass and energy. 20 Another tool used in negative ion beam measurements is the magnetized Faraday cup [21][22][23] using transversal magnetic field for electron suppression. This compact size device can be easily manufactured and integrated into a wide variety of experimental setups.…”
Section: Introductionmentioning
confidence: 99%
“…D ion are produced in a low‐pressure plasma source and subsequently extracted and accelerated. Recently, it has been demonstrated that carbon materials are interesting candidates to enhance negative ion production in hydrogen plasmas . In a series of papers, negative ion surface production mechanisms on hydrogenated carbon materials have been investigated, pointing out how Raman spectroscopy can be a useful tool for relating surface modification and ion production.…”
Section: Introductionmentioning
confidence: 99%